Arthroplasty of the lunate using bone marrow mesenchymal stromal cells - Berner, Arne (Springer-Verlag, 2010)
Mesenchymal stromal cells have the potential to differentiate into a variety of mesenchymal tissues such as bone, cartilage and ligaments. The potential for the regeneration of bone with cartilage coverage has still not been achieved. We evaluated the ability of bone marrow mesenchymal stromal cells to regenerate osteochondral defects in the cavity of the lunate in an animal model. Autologous mesenchymal stromal cells were harvested from the iliac crest of New Zealand white rabbits and expanded in vitro. Total lunate excision was performed in 24 animals and the isolated cells were loaded onto scaffolds. Cell-free scaffolds were implanted in the lunate space of the right wrists of all animals, and the left lunate spaces were filled with predifferentiated, cell-loaded scaffolds. Radiographic and histological analyses were performed after two, six and 12 weeks. In addition, the animals were injected with a fluorescent agent every five days, starting at day 30. After two and six weeks there was no radiographic evidence of ossification, whereas after 12 weeks all animals showed radiographic evidence of ossification. Histological sections showed increasing evidence of cartilage-like cell formation at the edges and new bone tissue in the centre of the newly formed tissue in all groups. The histological examinations showed that bone tissue was located around the newly incorporated vascularisation. This study demonstrated that newly formed vascularisation is necessary for the regeneration of bone tissue with cell-loaded scaffolds.